PROXIMATE ESTIMATION OF GENOTYPIC AND GENETIC (ADDITIVE) VARIANCES OF PLANT PRODUCTIVITY TRAITS - V. A. Dragavtsev; G. A. Makarova; A. A. Kochetov; G. V. Mirskaya; N. G. Sinyavina (Вавиловский журнал генетики и селекции)
For the first time all existent approaches to proximate estimation of genotypic variance are considered. A theory and methods of rapid estimation of genetic(additive) variance for prediction of transgressions in the course of breeding of self-pollinated plantsfor productivity traits are proposed.